The bathers (inverted) - Megan Francis Sullivan - Knoll, Valérie 1978- (Roma Publications, 2017)
This book extends from Megan Francis Sullivan's 2016 exhibition at Kunsthalle Bern, titled 'The Unanswered Question'. Its format refers to a publication by Ian Wilson from 1984, which also appeared at Kunsthalle Bern. Offering a showcase of her recent series of 'inverted' Cezanne paintings, this poetic object likewise gives a nod to the institutional framework of conceptual art, interweaving specific references to suggest the future negotiability of history. The publication has been designed by the artist together with HIT, and includes a text by Anne Rorimer.
500 Exemplare
Keywords: Sullivan, Megan -- 1975-; Ausstellungskatalog -- Kunsthalle Bern -- 23.04.2016-05.06.2016 -- Bern